Poly(vinyl acetate)-coated jute fabric reinforced polyester composite with enhanced mechanical performance: Interfacial hydrogen bond and autohesion mechanism. (February 2022) - Nath, Devarun; Debnath, Sayandeep; Datta, Mallika; Chakrabarti, Sumona; Ghosh, Shankha; Ghosh, Biman
The current research was conducted to determine the effect of pre-heating and coating of jute fabric with poly(vinyl acetate) for the improvement of the mechanical performance of jute fabric reinforced unsaturated polyester resin composite. Six different types of composites were manufactured through the implementation of hand lay-up method. The application level of 200 g of poly(vinyl acetate) per square meter of jute fabric leads to enhanced mechanical property of the composite. The optimum dose of coating showed improvement of 31%, 42.1%, and 35.7% in tensile strength, interlaminar shear strength, and flexural strength respectively in juxtaposition to preheated and untreated jute fabric-based the composite, whereas impact strength gained 59.7%. Such considerable increase in the mechanical performance is the result of strong interfacial adhesion ascribed to autohesion of unsaturated polyester resin with poly(vinyl acetate) and building of hydrogen bond between jute and poly(vinyl acetate) as supported by Fourier transform infrared spectroscopy. The optical microscopy of cross-sections of each sample revealed the homogeneity and distribution of coating thicknesses of poly(vinyl acetate). The characterisation of fractured surfaces of composite under tensile loading was carried out by scanning electron micrograph. The thermal behaviour of composite samples was examined by differential scanning calorimetry. The degree of curing of composite samples was typically found to be 72%. Water absorption reduced to its half by the virtue of gradual decrease in void content from 9.52% to 4.87%.